Assessing the Alternative Livelihood Options for Climate Change Vulnerable Coastal Fishing Villages in Kerala, India - Shyam S. Salim; Lina Joseph; Harsha Elizabeth James; A. M. Shinu; N. R. Athira and R. X. Smitha (International Journal of Environment and Climate Change, 2019)
Fisheries and allied sectors provide means of livelihood to millions of people around the world. In India more than 14.5 million individuals depend on fisheries for their livelihood, with Gujarat, Tamil Nadu and Kerala being the main three marine fish producing states of the country. The social and economic contribution of fisheries as a sector cannot be ignored or go unnoticed. Similarly the impact of climate change on fisheries and its resultant impact on the livelihood of fisheries dependent communities cannot be ignored. To address these pertinent issues, we first need to understand the impact of climate change on fisheries and the need of alternative livelihood options from the perspective of the direct stakeholders i.e. fishermen. This study is an endeavour to look at the need of Alternative livelihood options (ALOs) because of climate change among the coastal communities in Poonthura and Elamkunnapuzha villages of Thiruvananthapuram and Ernakulum respectively. Among the 222 marine fishing villages of Kerala, Poonthura and Elamkunnapuzha are the major fishing villages from the South West hotspot locales of India. The examination investigated different socioeconomic aspects, for example, fishing activity, basic household data, economic as well as historic and cultural dependence on fishing, employment and occupational structure, income distribution and assets, physical capital, financial capital, social capital, and exposure and awareness of the fishermen families to climate change by interviewing 1259 fishermen from Poonthura and Elamkunnapuzha. The study conducted in the most climate change vulnerable marine hotspots of Kerala (Elamkunnapuzha and Poonthura) explains the problems and prospects of the inhabitants in the sector and the importance of Alternative Livelihood Options (ALOs) in climate change adaptation.